Analisis Kesulitan Pembelajaran Tematik Pada Siswa Kelas IV Sekolah Dasar Negeri - Jelita, Anggia; Putra, Elpri Darta (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
This study aims to describe the thematic learning difficulties in fourth grade students and describe the difficulty factors that affect thematic learning difficulties in fourth grade students at SDN 014 Binjai Island. This type of research is descriptive qualitative research. Sources of data in this study were fourth grade teachers and 6 fourth grade students at SDN 014 Binjai Island. Data collection techniques used are interviews, observation and documentation. The data analysis technique uses the Milles and Huberman model with stages, data reduction, data presentation, and drawing conclusions. The results showed that there were six thematic learning difficulties in grade IV students, namely, 1) students felt confused, 2) students who had low cognitive/thinking power were left behind, 3) were less than optimal in receiving lessons, 4) parents had difficulties when helping. children study at home 5) students get low scores, and 6) students feel bored. While the difficulty factors that affect thematic learning difficulties at SDN 014 Binjai Island are eight, namely 1) lots of and mixed materials, 2) student learning styles, 3) HR (Human Resources), 4) student age, 5) thinking power. or students' cognitive, 6) parents, 7) long learning time, and 8) classroom atmosphere. The conclusion in this study is that there are still difficulties experienced by students related to thematic learning, this is due to a lot of influencing factors.